2018
DOI: 10.3390/molecules23123302
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Exerts Anticancer Effects Against Head and Neck Squamous Cell Carcinoma In Vitro

Abstract: Fucoidans have been reported to exert anticancer effects with simultaneous low toxicity against healthy tissue. That correlation was observed in several cancer models, however, it has never been investigated in head and neck cancer before. To magnify the efficacy of conventional therapy, the administration of agents like fucoidan could be beneficial. The aim of this study was to evaluate the anticancer effect of Fucus vesiculosus (FV) extract alone and with co-administration of cisplatin in head and neck squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…47 Our results demonstrated that fucoidan could induce G 2 phase arrest, similar to that obtained by Blaszczak et al using FaDu cells. 48 Other evidence is available indicating that fucoidan mediates cell death by inducing apoptosis. Treatment with a LMWF resulted in apoptosis in breast cancer cells due to decrease of antiapoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…47 Our results demonstrated that fucoidan could induce G 2 phase arrest, similar to that obtained by Blaszczak et al using FaDu cells. 48 Other evidence is available indicating that fucoidan mediates cell death by inducing apoptosis. Treatment with a LMWF resulted in apoptosis in breast cancer cells due to decrease of antiapoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies suggested that fucoidan, a sulfated polysaccharide extracted from brown algae, exerts the suppression of growth and proliferation of human cancer cells through apoptotic mechanisms (Atashrazm et al, 2016;Blaszczak et al, 2018;Han et al, 2015;Kim et al, 2010;Narayani et al, 2019;Park et al, 2011). Moreover, one study reported the effect of fucoidan in reducing the invasion of oral squamous cell carcinoma CAL27 cell line (Lin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is one of the cancers that can cause mortality worldwide (Torre et al, 2015). Smoking, tobacco use, alcohol consumption, and HPV infection are the risk factors of oral cavity cancer (Blot et al, 1988;Hashibe et al, 2009). Although treatment methods have developed over the last few decades, the prognosis for patients with OSCC is still moderate or poor.…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of cell proliferation inhibition, we used the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay as previously described [59]. Briefly, A2780 WT and CDDP (2000 cells/well), SK-OV-3 WT and CDDP (800 cells/well), and MRC-5 pd19 (3000 cells/well) were seeded onto a 96-well plate for overnight until the cells attached.…”
Section: Cell Viability Assaymentioning
confidence: 99%